Metabolic syndrome among Jaffna Tamil community, Sri Lanka - Sivarathy Amarasinghe; Balakumar Sandrasegarampillai; Vasanthy Arasaratnam (Indian Journal of Endocrinology and Metabolism, 2015)
Aim: The prevalence and associated risk factors of metabolic syndrome (MS) among adults over 18 years old in Jaffna district. Materials and Methods: It was community-based cross-sectional descriptive study. Multistage stratified cluster sampling technique was employed. An interviewer administered questionnaire was used to obtain the relevant information. Waist circumference (WC) and blood pressure (BP) measurements were recorded. Fasting plasma glucose (FPG), high-density lipoprotein (HDL), and triacylglycerols were analyzed by the enzymatic colorimetric assay using semi-automated analyzer (Teco Diagnostics TC-3300). International Diabetic Federation guideline for Asians was used to identify MS. Results: Sample response rate was 95.3% and of them, 43.8% (n = 224) was male. The prevalence of central obesity (WC for male ≥90 cm, female ≥80 cm) was 23.9%. Raised FPG (≥100 mg/dL, or previously diagnosed diabetes mellitus), hypertriacylglycerolemia (≥150 mg/dl), low level of HDL cholesterol (<40 mg/dL in males, <50 mg/dL in females), and raised BP (systolic BP ≥130 or diastolic BP ≥85 mmHg or previously diagnosed hypertension) were found in 23.9%, 25%, 79.3%, and 36.6% of the participants. The prevalence of MS was 15.8% (95% confidence interval [CI]: 12.8-19.3) and it was 17.4% in males and 14.6% in females. Participants living in the urban area had a higher prevalence of MS when compared with participants in a rural area (P = 0.015). Older age (P < 0.001) was a risk factor for development of MS. Smoking (P = 0.005) was a risk factor for the development of MS. Participants having sedentary, moderately active, and highly active lifestyle had the prevalence of MS 20.6% (95% CI: 13.2-29.7), 14.7% (95% CI: 10.6-19.5), and 14.7% (95% CI: 9.3-21.6), respectively (P = 0.247). Conclusion: Older age, urban living, and smoking carry a higher risk for development of MS among Jaffna Tamil community.